of tourism development in the South Caucasus: past and present - Tamarashvili, Tamar ("Intercultural Dialogues" Transactions, 2023)
The article `Aspects of tourism development in the South Caucasus: past and present covers the historical aspects of tourism development in the Caucasus region. The Caucasus region was and is distinguished by many tourist opportunities, characterized by a special geopolitical location, and an abundance and diversity of tourist resources. The archival materials give us an idea of the history and peculiarities of the development of tourism in the Caucasus. By studying and analyzing them, we get to know the peculiarities of the development of tourism in the Caucasus. In particular, studying the activities of the "Main Committee for the Promotion of Tourism in the Caucasus" gives us the opportunity to learn about foreign relations, the experience of foreigners, advice, recommendations, instructions, all of which were important for the development of the field. With the representatives of Switzerland, Bosnia-Herzegovina, sharing their experience provided the basis for the correct and rapid development of tourism in the Caucasus. Based on archival sources, we can discuss the variety of century-old forms of advertising, information media, tourism safety and sanitary-epidemiological issues, advertising forms, means of placement, types of transport, and tourism infrastructure. Today, there are many tourist organizations and time along with information technologies are changing, but the location of the Caucasus remains the same. It has multifaceted and interesting tourist potential. The beauty of the Caucasus, beautiful passes, nature, cuisine and traditions of hospitalityalways aroused the interest of foreigners. Furthermore, advice, recommendations of foreign experts in tourism, opinions formed by world tourism organizations, together with local tourism experts, are a necessary condition for the development and progress of tourism in any country.